MiR395c Regulates Secondary Xylem Development Through Sulfate Metabolism in Poplar - Liu, Chunhao; Ma, Ding; Wang, Zihao; Chen, Ningcong; Ma, Xiaoyun; He, Xin-Qiang (Frontiers in Plant Science, 2022)
Secondary xylem development requires the coordination of multiple regulatory factors, including plant hormones, transcription factors, and microRNAs (miRNAs). MiR395 is an important regulator involved in sulfate metabolism, but its function in plant development is unclear. This study investigated the functions of miR395c in the secondary xylem development in Populus alba × P. glandulosa. MiR395c was highly expressed in the shoot apex and secondary xylem. The overexpression of miR395c resulted in an increase in both secondary xylem width and vessel dimension, as well as a decrease in the thickness of the secondary cell wall of the xylem fiber. Further analysis showed that miR395c inhibited biosynthesis of sulfate metabolic products by targeting ATPS genes, which led to the reduction of Abscisic acid (ABA) synthesis and down-regulation of MYB46 expression. Our results indicate that miR395c regulates the secondary xylem development process via sulfate metabolism in Populus.